Pengembangan Daya Saing Sekolah melalui Analisis SWOT: Kajian pada SDIT Thoriqul Jannah Sinjai - Muallim (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2026)
This study examines the development of school competitiveness through SWOT analysis, focusing on SDIT Thoriqul Jannah in Sinjai. In the increasingly competitive educational environment, schools are required to maintain and enhance their competitiveness, especially in areas such as location, pricing, services, and promotion. The study aims to identify the strengths, weaknesses, opportunities, and threats (SWOT) of the school in these four aspects and to formulate strategies for improving its competitive position. A qualitative descriptive research method was employed, with data collected through semi-structured interviews, observations, and documentation. The findings highlight the school's strengths, such as its secure and conducive learning environment, affordable pricing, and strong community engagement. However, the study also identifies weaknesses, including limited accessibility, the need for more flexible payment schemes, and the underutilization of technology in services. The research concludes with strategic recommendations for the school to improve its competitiveness, such as enhancing the use of digital media for promotion, strengthening partnerships with parents and local communities, and optimizing its service quality to meet the growing demands of the educational market. This research contributes to the theoretical understanding of school management strategies and provides practical recommendations for educational institutions seeking to improve their competitiveness in a rapidly evolving market